Anti-static single layer sheet, or Anti-static single layer film, and Anti-static multilayer sheet

The antistatic single-layer and multi-layer sheets, formulated with a polymeric antistatic agent and thermoplastic resin, address the static electricity challenges in biomass-based plastics by maintaining excellent antistatic properties even after reheating.

JP2025062678APending Publication Date: 2025-04-15KOBAYASHI & CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023171854
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-03
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Plastics molded from resin compositions containing biomass materials often suffer from static electricity issues due to friction, leading to dust and dirt adsorption, aesthetic damage, and equipment malfunction. Additionally, these materials fail to maintain antistatic properties after reheating.

Method used

The development of an antistatic single-layer sheet or film and an antistatic multi-layer sheet, utilizing a resin composition containing a polymeric antistatic agent. This composition includes a thermoplastic resin and a nonionic polymeric antistatic agent with polyethylene oxide chains, ensuring excellent antistatic properties that are maintained even after reheating.

Benefits of technology

The proposed solution effectively provides antistatic single-layer sheets or films and multi-layer sheets with surface resistance values of 10 Ω or less, which are maintained after heating at 200°C for 5 minutes, thereby preventing static-related issues and ensuring reliable performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062678000001
    Figure 2025062678000001
  • Figure 2025062678000002
    Figure 2025062678000002
  • Figure 2025062678000003
    Figure 2025062678000003
Patent Text Reader

Abstract

To provide an anti-static single layer sheet, or an antistatic single layer film, and an anti-static multilayer sheet having excellent antistatic property.SOLUTION: An antistatic single-layer sheet or an antistatic single-layer film is formed from a polymer type anti-static agent-containing resin composition containing a polymer type anti-static agent. The polymer type anti-static agent is a nonionic polymer type anti-static agent. The nonionic polymer type anti-static agent is incorporated with a polyethylene oxide chain. The surface resistance value on at least one principal plane is 1012.5 Ω or lower. An antistatic multilayer sheet includes: a biomass material-containing layer; and an anti-static layer formed on at least one principal plane of the biomass material-containing layer, where the biomass material-containing layer is formed from a biomass material-containing resin composition containing a biomass material, and the anti-static layer is formed from the anti-static agent-containing resin composition containing the polymer type anti-static agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present technology relates to an antistatic monolayer sheet or an antistatic monolayer film and an antistatic multilayer sheet. More specifically, the present technology relates to an antistatic monolayer sheet or an antistatic monolayer film and an antistatic multilayer sheet having excellent antistatic properties even after reheating. [Background technology]

[0002] Plastic molded products manufactured from petroleum resources and other raw materials are used for a wide range of applications, including food and beverage containers, various packaging materials such as sheets and films, cushioning materials, daily necessities, agricultural products, and other industrial materials. Plastic molded products are made from fossil resources, and the depletion of these raw materials is an important long-term issue. In addition, plastic molded products emit carbon dioxide when burned at the time of disposal, and the suppression of global warming caused by carbon dioxide is an important issue.

[0003] Today, natural materials are attracting attention as new, environmentally friendly materials that can serve as an alternative to petroleum as a raw material for plastic molded products, emit less carbon dioxide when disposed of, and have no impact on global warming. As one means of solving the problems of pollution caused by global warming and resource depletion, attention has been focused on biotechnology, which has made great advances in recent years, and particular efforts are being made to utilize biomass materials, which are organic resources derived from living organisms.

[0004] As such biomass materials, the use of natural materials such as polylactic acid, starch, modified starch, cellulose, etc. Biomass materials emit little carbon dioxide even when burned at the time of disposal and do not have a negative impact on the environment.

[0005] In order to improve the physical properties and processability and to enable replacement of plastic molding materials, composite materials have been developed in which polylactic acid, biopolyethylene, starch, and cellulose made from biomass materials are combined with synthetic resin materials such as polyolefins (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2001-64458 A [Patent Document 2] JP 2004-155842 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, plastics molded from resin compositions containing biomass materials generally have electrical insulating properties and therefore become charged with static electricity due to friction, etc. Static electricity can attract dust and dirt in the air, marring the aesthetic appearance of the plastic, or cause plastic films to stick together, resulting in malfunction of electrical equipment.

[0008] In order to solve the problems caused by static electricity, an antistatic agent has been blended into a biomass material-containing resin composition, but there is a problem that sufficient antistatic properties cannot be obtained because the biomass material contained in the resin composition absorbs the antistatic agent, etc. There is also a problem that the antistatic properties cannot be maintained after reheating due to vacuum molding, etc.

[0009] An object of the present technology is to provide an antistatic single-layer sheet or antistatic single-layer film and an antistatic multilayer sheet having excellent antistatic properties. [Means for solving the problem]

[0010] This technology is Provided is an antistatic single-layer sheet or an antistatic single-layer film formed from an antistatic agent-containing resin composition that contains a polymer-type antistatic agent. The polymeric antistatic agent may be a non-ionic polymeric antistatic agent. The non-ionic polymeric antistatic agent may have polyethylene oxide chains incorporated therein. The antistatic single-layer sheet or antistatic single-layer film has a surface resistance of 10 or more on at least one main surface. 12.5 It can be less than Ω. The antistatic monolayer sheet or film may have an average thickness of 1500 μm or less. The antistatic single-layer sheet or antistatic single-layer film has a surface resistance of 10 or more on at least one of its main surfaces after being heated for 5 minutes in an environment at a temperature of 200°C. 12.5 It can be less than Ω. In addition, this technology: a biomass material containing layer; an antistatic layer formed on at least one major surface of the biomass material-containing layer; A multilayer sheet having The biomass material-containing layer is formed from a biomass material-containing resin composition containing a biomass material, The present invention also provides an antistatic multilayer sheet, in which the antistatic layer is formed from an antistatic agent-containing resin composition that contains a polymeric antistatic agent. The polymeric antistatic agent may be a non-ionic polymeric antistatic agent. The non-ionic polymeric antistatic agent may have a polyethylene oxide chain incorporated therein. The antistatic multilayer sheet has a surface resistance of 10 or more on at least one main surface. 12.5 It can be less than Ω. In the antistatic multilayer sheet, the antistatic layer may have an average thickness of 100 μm or less. The antistatic multilayer sheet has a surface resistance of 10 or more on at least one of its main surfaces after being heated for 5 minutes in an environment at a temperature of 200°C. 12.5 It can be less than Ω. The biomass material can be starch. The antistatic layer may be formed on both major surfaces of the biomass material-containing layer. Effect of the Invention

[0011] According to the present technology, it is possible to obtain an antistatic single-layer sheet or an antistatic single-layer film and an antistatic multilayer sheet having excellent antistatic properties. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a cross-sectional view illustrating an antistatic multilayer sheet according to a second embodiment of the present technology. [Diagram 2] FIG. 4 is a schematic diagram showing an example of a multi-layer co-extrusion molding machine used in the manufacturing method of the antistatic multilayer sheet according to the second embodiment. [Diagram 3] FIG. 11 is a cross-sectional view illustrating an antistatic multilayer sheet according to a third embodiment of the present technology. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Preferred embodiments for carrying out the present technology will be described below. Note that the embodiments described below are representative embodiments of the present technology, and the scope of the present technology is not limited to these embodiments.

[0014] This technology will be described in the following order. 1. First embodiment (example of antistatic single layer sheet or antistatic single layer film) (1) Structure of antistatic single-layer sheet or antistatic single-layer film (2) Physical properties (3) Method for producing antistatic monolayer sheet or antistatic monolayer film 2. Second embodiment (example of antistatic multilayer sheet) (1) Composition of antistatic multi-layer sheet (2) Physical properties (3) Manufacturing method of antistatic multilayer sheet 3. Third embodiment (another example of antistatic multilayer sheet) (1) Composition of antistatic multi-layer sheet (2) Physical properties (3) Manufacturing method of antistatic multilayer sheet 4. Working Example

[0015] 1. First embodiment (example of antistatic single layer sheet or antistatic single layer film)

[0016] (1) Structure of antistatic single-layer sheet or antistatic single-layer film

[0017] The antistatic single layer sheet or antistatic single layer film according to the present embodiment is formed from an antistatic agent-containing resin composition containing a polymeric antistatic agent. The antistatic agent-containing resin composition contains a resin and an antistatic agent. Each component will be described below.

[0018] (resin)

[0019] In the antistatic single-layer sheet or antistatic single-layer film according to the present embodiment, the resin contained in the antistatic agent-containing resin composition is preferably a thermoplastic resin. Such a thermoplastic resin may be an olefin-based resin, a polyester-based resin, or a mixture of these resins. The thermoplastic resin may be a polystyrene-based resin.

[0020] The olefin resin is a polymer obtained by polymerization of olefins (e.g., α-olefins) as the main monomers. The olefin resin may be, for example, a polyethylene (PE) resin, a polypropylene (PP) resin, or a combination thereof.

[0021] The polyethylene resin may be, for example, an ethylene copolymer such as low density polyethylene resin (LDPE: Low Density Polyethylene), high density polyethylene resin (HDPE: High Density Polyethylene), very low density polyethylene resin (VLDPE: Very Low Density Polyethylene), linear low density polyethylene resin (LLDPE: Linear Low Density Polyethylene), ethylene-vinyl acetate copolymer (EVA resin), or ultra high molecular weight polyethylene resin (UHMW-PE: Ultra High Molecular Weight-Polyethylene), or a combination thereof.

[0022] The polypropylene resin may be, for example, a homopolymer polypropylene resin, or a random or block copolymer polypropylene resin (eg, an ethylene-propylene copolymer, etc.), or a combination thereof.

[0023] The olefin resin may be preferably a polyolefin resin derived from biomass (e.g., a biomass-derived polyethylene resin, etc.), for example, a biomass polyethylene resin. The biomass polyethylene resin may be, for example, LDPE, LLDPE, or HDPE. This can reduce CO2 emissions.

[0024] The olefin resin may be a metallocene-catalyzed olefin resin, i.e., the thermoplastic resin may be, for example, a metallocene-catalyzed polyethylene resin or polypropylene resin, or a combination thereof. The polystyrene-based resin may be a metallocene-catalyzed polystyrene-based resin.

[0025] The polyester resin is a polymer in which monomers are polymerized through ester bonds. The polyester resin may be, for example, polyethylene terephthalate resin (PET), polyethylene naphthalate resin (PEN), polybutylene terephthalate resin (PBT), polylactic acid resin (PLA), polycarbonate resin (PC), polybutylene adipate terephthalate resin (PBAT), polybutylene succinate resin (PBS), polyhydroxyalkanoate resin (PHA), or a combination of two or more of these.

[0026] The polystyrene resin is a polymer formed by polymerization of a styrene monomer. The polystyrene resin may be, for example, a polystyrene resin, a rubber-reinforced polystyrene resin (high impact polystyrene resin, HIPS), an acrylonitrile-styrene copolymer (AS resin), a methacrylate ester-styrene copolymer, an acrylonitrile-acrylic rubber-styrene copolymer, an acrylonitrile-ethylene propylene-styrene copolymer, or a combination of two or more of these.

[0027] In this embodiment, the type of thermoplastic resin may be appropriately selected by a person skilled in the art depending on, for example, the application of the antistatic single-layer sheet or antistatic single-layer film.

[0028] In this embodiment, the thermoplastic resin preferably has a melting point of 90° C. to 180° C., and more preferably has a melting point of 95° C. to 170° C. By using a thermoplastic resin with a lower melting point, the molding temperature can be lowered.

[0029] The antistatic agent-containing resin composition may further contain other components, such as a low melting point additive, a high melting point additive, a compatibilizer, and a colorant.

[0030] The low melting point additive refers to an additive that has a melting point lower than the melting temperature of the resin and melts at a relatively low temperature.

[0031] The content of the low-melting-point additive is preferably 0.1% by mass to 5% by mass, and more preferably 0.1% by mass to 3% by mass, based on the mass of the antistatic agent-containing resin composition.

[0032] The antistatic agent-containing resin composition may also contain a high-melting additive. The high-melting additive refers to an additive having a higher melting point than the low-melting additive. Such a high-melting additive may have a higher melting point than the low-melting additive, preferably in the range of 100 to 150°C, solidify before the low-melting additive, and have a melting point lower than the melting temperature of the thermoplastic resin. Examples of such high-melting additives include fatty acid metal salts, hydrocarbons, higher alcohols, aliphatic amides, and fatty acid esters. Specifically, magnesium stearate, zinc stearate, calcium stearate, aluminum stearate, sodium lauryl sulfate, magnesium lauryl sulfate, potassium benzoate, sodium benzoate, and sodium stearyl fumarate are used.

[0033] The content of the high-melting point additive is, for example, preferably 0.1% by mass to 10% by mass, and more preferably 0.1% by mass to 5% by mass, based on the mass of the antistatic agent-containing resin composition.

[0034] The compatibilizer can be used to disperse the biomass material more uniformly in the antistatic agent-containing resin composition. The compatibilizer may be selected according to the type of resin contained in the antistatic agent-containing resin composition. Examples of the compatibilizer include acid-modified polyolefin, acid-modified nylon, acid-modified polystyrene, acid-modified EVA, acid-modified ethylene copolymer, acid-modified acrylate, acrylic acid-modified EVA, and modified ethylene acrylate.

[0035] When the resin contained in the antistatic agent-containing resin composition is a polyolefin resin, the compatibilizer is preferably an acid-modified polyolefin, and in particular may be a carboxylic acid anhydride-modified polyolefin or an olefin comonomer. The carboxylic anhydride constituting the carboxylic anhydride-modified polyolefin may preferably be maleic anhydride. The compatibilizer may be, for example, a maleic anhydride-grafted polyolefin resin, more particularly, one or a combination of two or more selected from the group consisting of maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, and maleic anhydride-modified ethylene-propylene copolymer. A rubber component may be dispersed in the compatibilizer. The content of the compatibilizer is preferably 0.1 to 10 parts by mass, and more preferably 1.0 to 5.0 parts by mass, per 100 parts by mass of the antistatic agent-containing resin composition.

[0036] The colorant can be used to impart color to the antistatic agent-containing resin composition. Examples of the colorant include titanium oxide, carbon black, dyes, and pigments.

[0037] As the other components, for example, an antioxidant and an impact resistance agent may be used. As the antioxidant and the impact resistance agent, various commercially available antioxidants and impact resistance agents may be used.

[0038] (Polymer-type antistatic agent)

[0039] In the antistatic monolayer sheet or antistatic monolayer film according to the present embodiment, the polymeric antistatic agent contained in the antistatic agent-containing resin composition refers to a polymeric compound in which a hydrophilic unit is introduced as a conductive unit in the molecule. Such polymeric antistatic agents are classified into nonionic polymeric antistatic agents (polyether ester amide type, ethylene oxide-epichlorohydrin type, polyether ester type), anionic polymeric antistatic agents (polystyrene sulfonic acid type), and cationic polymeric antistatic agents (quaternary ammonium base-containing acrylate polymer type) according to the conductive unit (hydrophilic unit) introduced. In the present embodiment, nonionic polymeric antistatic agents are preferred, particularly from the viewpoint of maintaining the antistatic effect even after reheating. As nonionic polymeric antistatic agents, in particular, polyether ester amide (PEEA), ethylene oxide-epichlorohydrin (EO-ECH) copolymer, polyether ester (PEE), etc., in which a polyethylene oxide (PEO) chain or the like is incorporated as a conductive unit in the molecule, are preferred. Commercially available non-ionic polymer-type antistatic agents include "Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd." and "Pelestat (registered trademark) 300, manufactured by Sanyo Chemical Industries, Ltd.".

[0040] In the present embodiment, from the viewpoint of antistatic properties, the content of the polymer-type antistatic agent is preferably 3% by mass or more, more preferably 8% by mass or more, even more preferably 12% by mass or more, and even more preferably 17% by mass or more, based on the mass of the antistatic agent-containing resin composition. Also, the content of the polymer-type antistatic agent is preferably 45% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less, based on the mass of the antistatic agent-containing resin composition.

[0041] The antistatic agent-containing resin composition may further contain other components as long as the antistatic properties are not impaired. Examples of the other components include a compatibilizer and a colorant. The content of the other components is preferably appropriately adjusted so as not to impair the antistatic properties.

[0042] (2) Physical properties

[0043] [Surface resistance value]

[0044] The antistatic single-layer sheet or antistatic single-layer film according to this embodiment has a surface resistance of preferably 10 12.5 Ω or less, more preferably 10 12 Ω or less, more preferably 10 11 Ω or less, and even more preferably 10 10 Ω or less. The surface resistance value refers to the resistance value of the surface of the antistatic single-layer sheet or antistatic single-layer film. The surface resistance value can be measured, for example, using a commercially available surface resistance meter (ST-4, manufactured by SIMCO).

[0045] In order to maintain the antistatic properties after the antistatic single-layer sheet or antistatic single-layer film according to the present embodiment is reheated in vacuum molding or the like, the antistatic single-layer sheet or antistatic single-layer film according to the present embodiment has a surface resistance of preferably 10 or more on at least one main surface after heating for 5 minutes in an environment at a temperature of 200°C. 12.5 Ω or less, more preferably 10 12 Ω or less, more preferably 10 11 Ω or less, and even more preferably 10 10 It is less than Ω.

[0046] (3) Method for producing antistatic monolayer sheet or antistatic monolayer film

[0047] The method for producing the antistatic single-layer sheet or antistatic single-layer film according to the present embodiment includes a step of preparing an antistatic agent-containing resin composition and a molding step. Each step will be described below.

[0048] <Antistatic agent-containing resin composition preparation step (S1)>

[0049] In this step, the polymer-type antistatic agent and the resin are mixed to prepare an antistatic agent-containing resin composition. Note that the polymer-type antistatic agent and the resin are the same as those described in 1.(1) above, so the description of the polymer-type antistatic agent and the resin is omitted here.

[0050] In this step, the polymer-type antistatic agent and the resin are mixed. When mixing the polymer-type antistatic agent and the resin, for example, the polymer-type antistatic agent and the resin may be simply mixed in a dry state to prepare a polymer-type antistatic agent-containing resin composition which is a mixture of a powdered polymer-type antistatic agent and a pellet-shaped resin. Alternatively, the dried polymer-type antistatic agent and the resin may be simultaneously fed into an extruder via a feeder, and the rotation speed, stirring time, temperature, etc. may be controlled, and the polymer-type antistatic agent and the resin may be uniformly kneaded and mixed by heating and kneading, so that the mixture of the polymer-type antistatic agent and the resin in a melt-kneaded state present in the extruder is made into a polymer-type antistatic agent-containing resin composition. Furthermore, the mixture of the polymer-type antistatic agent and the resin in a melt-kneaded state may be extruded from the extruder, cooled, and pelletized to make the polymer-type antistatic agent-containing resin composition. As such an extruder, a single-screw extruder or a twin-screw extruder may be used. In addition, when the polymer-type antistatic agent and the resin are fed into the extruder, additives may be fed at the same time, and examples of such additives include low-melting-point additives and high-melting-point additives. In addition, the polymer-type antistatic agent, the resin, and the additives may be fed individually in predetermined blending amounts via feeders.

[0051] When the polymer-type antistatic agent and the resin are mixed in the extruder, the heat processing temperature (cylinder temperature) may be set to a temperature lower than the temperature at which the resin melts or higher than the melting point of the high-melting additive, from the viewpoint of suppressing deterioration and discoloration of the materials. For example, the heat processing temperature (cylinder temperature) may be set to 100 to 190°C.

[0052] <Molding process (S2)>

[0053] In this step, the antistatic agent-containing resin composition prepared in the antistatic agent-containing resin composition preparation step (S1) is molded to obtain an antistatic single-layer sheet or an antistatic single-layer film. For example, in the antistatic agent-containing resin composition preparation step (S1), a polymer-type antistatic agent and a resin are sufficiently heated and mixed in an extruder to prepare an antistatic agent-containing resin composition, and then the antistatic agent-containing resin composition is transferred to a molding machine, and the antistatic agent-containing resin composition is molded using the molding machine to form an antistatic single-layer sheet or an antistatic single-layer film. The temperature when molding the antistatic single-layer sheet or antistatic single-layer film may be set to preferably higher than the melting temperature of the resin, for example, 150 to 220 ° C., and the molding pressure may be appropriately set.

[0054] When forming the antistatic monolayer sheet or antistatic monolayer film, various molding machines such as a T-die extruder, a calendar molding machine, and an inflation machine can be used in the molding process. The antistatic agent-containing resin composition formed into, for example, a sheet or film by the molding machine may be immediately cooled by appropriately setting the temperature of the take-up roll to a predetermined thickness after molding, and taken up and wound up as a raw roll. The average thickness of the monolayer sheet according to this embodiment is preferably 300 μm or more, more preferably 350 μm or more, and even more preferably 400 μm or more, and preferably 1500 μm or less, more preferably 1400 μm or less, and even more preferably 1000 μm or less. The average thickness of the antistatic monolayer film according to this embodiment is preferably 250 μm or less, more preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. The average thickness of the antistatic monolayer film according to this embodiment is preferably 5 μm or more, and more preferably 10 μm or more.

[0055] 2. Second embodiment (example of antistatic multilayer sheet)

[0056] (1) Composition of antistatic multi-layer sheet

[0057] The antistatic multilayer sheet according to this embodiment has a biomass material-containing layer and an antistatic layer formed on at least one main surface of the biomass material-containing layer. Hereinafter, the antistatic multilayer sheet according to this embodiment will be described with reference to the drawings. FIG. 1 is a schematic cross-sectional view of the antistatic multilayer sheet according to this embodiment. As shown in FIG. 1, the antistatic multilayer sheet 10 according to this embodiment is an antistatic multilayer sheet having a two-layer structure including a biomass material-containing layer 11 and an antistatic layer 12. The antistatic layer 12 is formed on at least one main surface of the biomass material-containing layer 11. Hereinafter, the biomass material-containing layer and the antistatic layer constituting the antistatic multilayer sheet according to this embodiment will be described.

[0058] [Biomass material-containing layer]

[0059] First, the biomass material-containing layer will be described. The biomass material-containing layer is formed from a biomass material-containing resin composition that contains a biomass material. The biomass material-containing resin composition contains a biomass material and a resin.

[0060] (Biomass materials)

[0061] <Plant-derived biomass materials>

[0062] In the antistatic multilayer sheet according to the present embodiment, the biomass material contained in the biomass material-containing resin composition may be a plant-derived biomass material or a biologically derived biomass material. Examples of the plant-derived biomass material include a starch material and a cellulose material. The starch material and the cellulose material may be classified as waste biomass, unused biomass, or resource grain.

[0063] The starch material may include starch from underground starch and starch from aboveground starch. Underground starch is starch accumulated underground, for example, in rhizomes or roots. Examples of underground starch include, but are not limited to, tapioca starch (cassava starch), potato starch, sweet potato starch, kudzu starch, and bracken starch.

[0064] Terrestrial starch refers to starch accumulated above ground, for example, starch accumulated in seeds, etc. Terrestrial starches include, but are not limited to, corn starch, wheat starch, sago starch, acorn starch, and rice starch.

[0065] The starch material may be a modified starch (i.e., modified starch), particularly a modified starch of underground starch. Such modified starch may be physically modified, or chemically modified, for example. Examples of physically modified starch include alpha-starch and heat-moisture starch. Examples of chemically modified starch include acetoacetate esterified starch, acetate esterified starch, hydroxymethyl etherified starch, hydroxypropyl etherified starch, carboxymethyl etherified starch, allyl etherified starch, methyl etherified starch, succinate esterified starch, xanthogen acetate esterified starch, nitrate esterified starch, urea phosphate esterified starch, phosphate esterified starch, phosphate cross-linked starch, formaldehyde cross-linked starch, acrolein cross-linked starch, epichlorohydrin cross-linked starch, etc.

[0066] When the starch material is corn starch, the upper limit of the particle size is preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less, from the viewpoint of dispersibility.

[0067] When the starch material is tapioca starch, from the viewpoint of dispersibility, the upper limit of the particle size is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 25 μm or less.

[0068] When the starch material is potato starch, from the viewpoint of dispersibility, the upper limit of the particle size is preferably 80 μm or less, more preferably 60 μm or less, and even more preferably 40 μm or less.

[0069] The starch material may preferably contain equilibrium moisture, for example, preferably 10% to 15% by mass, more preferably 10% to 14% by mass, even more preferably 10% to 13% by mass, and even more preferably 11% to 13% by mass, based on the mass of the starch material.

[0070] In this embodiment, the content of the starch material is 5% by mass or more, preferably 15% by mass or more, more preferably 20% by mass or more, and even more preferably 25% by mass or more, based on the mass of the biomass material-containing resin composition. Also, the content of the starch material is preferably 60% by mass or less, more preferably 45% by mass or less, even more preferably 40% by mass or less, and even more preferably 35% by mass or less, based on the mass of the biomass material-containing resin composition.

[0071] The cellulosic materials may include paper, paper pulp, cotton, or ground cloth.

[0072] The particle size D50 (median diameter) of the cellulose material may be, for example, 15 μm to 150 μm, and particularly preferably 20 μm to 100 μm. The particle size D50 is determined by wet measurement using a laser diffraction particle size distribution measuring device (SALD-3100, Shimadzu Corporation). The cellulose material having a particle size within the above numerical range can contribute to improving the dispersibility of the cellulose material contained in the biomass material-containing resin composition.

[0073] According to this embodiment, the number of cellulose fibers having a particle size of 9.8 μm to 110.6 μm among the cellulose fibers constituting the cellulose material is 65% to 100%, preferably 70% to 100%, more preferably 80% to 100%, and even more preferably 85% to 100% of the total number of cellulose fibers constituting the cellulose material. The above ratio regarding the number of cellulose fibers is obtained by determining the ratio of the number of cellulose fibers having a particle size of 0 μm to 9.8 μm (hereinafter referred to as the "first ratio") and the ratio of the number of cellulose fibers having a particle size of 0 μm to 110.6 μm (hereinafter referred to as the "second ratio") among the total number of cellulose fibers in the cellulose material by wet measurement using the laser diffraction type particle size distribution measuring device, and subtracting the first ratio from the second ratio. The numerical ranges "0 μm to 9.8 μm" and "0 μm to 110.6 μm" are both numerical ranges input to the laser diffraction type particle size distribution measuring device in the wet measurement. In this embodiment, it is particularly preferable that the number of cellulose fibers having a particle size of 110.6 μm to 998.4 μm among the cellulose fibers constituting the cellulose material is 0% to 30%, preferably 0% to 25%, more preferably 0% to 20%, and even more preferably 0% to 15% of the total number of cellulose fibers constituting the cellulose material. The above ratio regarding the number of cellulose fibers is obtained by determining the ratio of the number of cellulose fibers having a particle size of 0 μm to 110.6 μm (the above-mentioned "second ratio") and the ratio of the number of cellulose fibers having a particle size of 0 μm to 998.4 μm (hereinafter referred to as "third ratio") among the total number of cellulose fibers in the cellulose material by wet measurement using the laser diffraction type particle size distribution measuring device, and subtracting the second ratio from the third ratio. The numerical ranges "0 μm to 110.6 μm" and "0 μm to 998.4 μm" are both numerical ranges input to the laser diffraction type particle size distribution measuring device in the wet measurement. The cellulose material having the above particle size distribution can be produced, for example, by treating pulp with a chemical such as an acid. An example of the cellulose material having the above particle size distribution is KC Flock W400 (Nippon Paper Industries Co., Ltd.). The use of cellulose powder having the above particle size distribution provides better moldability when molding the biomass material-containing layer. In particular, among the cellulose fibers constituting the cellulose powder, the number of cellulose fibers having a particle size of 9.8 μm to 110.6 μm accounts for 80% to 100%, and even more preferably 85% to 100%, of the total number of cellulose fibers constituting the cellulose powder, thereby preventing the occurrence of tears or holes in the biomass material-containing layer obtained by molding the biomass material-containing resin composition. In order to prevent the occurrence of tears or holes in the biomass material-containing layer, particularly preferably, among the cellulose fibers constituting the cellulose powder, the number of cellulose fibers having a particle size of 110.6 μm to 998.4 μm accounts for 0% to 20%, and even more preferably 0% to 15%, of the total number of cellulose fibers constituting the cellulose powder.

[0074] According to another preferred embodiment of the present invention, the cellulose powder may have a particle size in which 90% or more pass through a 100 mesh. In this embodiment, more preferably, the cellulose powder may have a particle size in which 90% or more pass through a 100 mesh, and the apparent specific gravity of the cellulose powder may be 0.30 g / ml to 0.40 g / ml.

[0075] The particle size is measured by the standard sieve method, specifically as follows: 10 g of sample is placed in a 100 mesh standard sieve, a tray and a lid are placed on the standard sieve, and the sample is shaken for 40 minutes in a low tap shaker. The particle size is calculated from the sample mass (10 g) and the mass of the residue on the sieve by the following formula. Particle size (%) = [(sample mass (g) - sieve residue (g)) / sample mass (g)] x 100

[0076] The apparent specific gravity is measured as follows. That is, 10 g of a sample is accurately weighed on a balance and placed in a 50 ml graduated cylinder. The bottom of the graduated cylinder is placed on a rubber sheet-covered platform and tapped while taking care not to scatter the sample. The tapping is continued until the sample no longer clogs. After the tapping, the surface of the sample is flattened and the scale (volume, ml) is read. The apparent specific gravity is then calculated using the following formula: Apparent specific gravity (g / ml) = sample (10g) / volume (ml)

[0077] The cellulose powder having the above particle size (or the above particle size and the above apparent specific gravity) can be produced, for example, by mechanically grinding pulp (for example, jet mill grinding). An example of the cellulose powder having the above particle size (or the above particle size and the above apparent specific gravity) is KC Flock 100GK.

[0078] In this embodiment, the content of the cellulose material is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the mass of the biomass material-containing resin composition. Also, the content of the cellulose material is preferably 45% by mass or less, more preferably 35% by mass or less, even more preferably 30% by mass or less, and even more preferably 25% by mass or less, based on the mass of the biomass material-containing resin composition.

[0079] <Biomass materials derived from living organisms>

[0080] Examples of biomass materials derived from living organisms include shell powder. Shell powder refers to shells crushed into powder. Shells are not particularly limited, and shells of shellfish such as scallops, oysters, surf clams, abalone, mussels, clams, and mussels can be used. Shell powder may be obtained, for example, by washing and sterilizing shells discarded from food factories and then crushing them, or may be obtained from shells of shellfish other than those used for food. The method for crushing shells is not particularly limited, and any known crushing method may be appropriately selected and adopted, and may be wet or dry. Shells may also be pre-crushed in a coarse crusher and then powdered in a crusher. Specifically, examples of coarse crushers include jaw crushers, cone crushers, cutter mills, hammer crushers, and the like, and examples of crushers include roll mills, stamp mills, hammer mills, ball mills, vibrating ball mills, roller mills, vertical mills, and the like. The shell powder may preferably be scallop shell powder. Examples of scallop shell powder include unbaked scallop shell powder and baked scallop shell powder. Unbaked scallop shell powder is made by powdering natural scallop shells and is in an unbaked state that has not been baked, and is usually composed mainly of calcium carbonate (about 96%). Unbaked scallop shell powder is commercially available.

[0081] From the viewpoint of improving mixability with other components contained in the biomass material-containing resin composition, the shell powder may have an average particle size of preferably 1 to 100 μm, more preferably 5 to 50 μm, and even more preferably 10 to 20 μm.

[0082] The content of the shell powder may be preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the mass% of the biomass material-containing resin composition. The upper limit of the content of the shell powder may be, for example, preferably 75% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 55% by mass or less, based on the mass% of the biomass material-containing resin composition, taking into consideration the physical properties of the antistatic multilayer sheet.

[0083] [Antistatic layer]

[0084] Next, the antistatic layer will be described. The antistatic layer is formed from an antistatic agent-containing resin composition containing a polymer-type antistatic agent. Note that the description of the antistatic agent-containing resin composition in 1.(1) above applies to the antistatic agent-containing resin composition, so the description of the antistatic agent-containing resin composition will be omitted.

[0085] (2) Physical properties

[0086] As shown in Fig. 1, the antistatic multilayer sheet 10 according to this embodiment is an antistatic multilayer sheet having a two-layer structure including a biomass material-containing layer 11 and an antistatic layer 12. The antistatic multilayer sheet 10 has two main surfaces S1 and S2. The antistatic multilayer sheet 10 according to this embodiment has a surface resistance of preferably 10 on the main surface S1 of the antistatic layer 12 opposite to the main surface S3 on which the biomass material-containing layer 11 is formed. 12.5 Ω or less, more preferably 10 12 Ω or less, more preferably 10 11 Ω or less, and even more preferably 10 10 It is less than Ω.

[0087] In order to maintain the antistatic properties after the antistatic multilayer sheet is reheated in vacuum molding or the like, the antistatic multilayer sheet according to the present embodiment has a surface resistance of preferably 10 or more on at least one main surface after being heated for 5 minutes in an environment at a temperature of 200°C. 12.5 Ω or less, more preferably 10 12 Ω or less, more preferably 10 11 Ω or less, and even more preferably 10 10 It is less than Ω.

[0088] (3) Manufacturing method of antistatic multilayer sheet

[0089] The method for producing the antistatic multilayer sheet according to the second embodiment can include a biomass material drying step (S1), a resin composition preparation step (S2), and a multilayer extrusion molding step (S3).

[0090] The method for producing the antistatic multilayer sheet according to the present embodiment may include, for example, a biomass material drying step in which a biomass material is accommodated in a container equipped with an external heating unit, and the inside of the container is heated by the heating unit while stirring to dry the biomass material; a resin composition preparation step in which the biomass material dried in the biomass material drying step is mixed with a resin to prepare a biomass material-containing resin composition; and a multilayer extrusion molding step in which the biomass material-containing thermoplastic resin composition prepared in the resin composition preparation step and an antistatic agent-containing resin composition are multilayer extrusion molded to obtain an antistatic multilayer sheet in which a biomass material-containing layer and an antistatic layer are laminated. Note that a biomass material cooling step may be provided between the biomass material drying step and the resin composition preparation step. In the cooling step, the mixture of the biomass material and the resin may be transferred to a cooling agitator and cooled to a temperature equal to or higher than the melting temperature of the low-melting additive while being stirred in the cooling agitator. Note that the mixture of the biomass material and the resin may be cooled without stirring.

[0091] The method for producing the antistatic multilayer sheet according to the second embodiment may include a biomass material drying step (S1), a resin composition preparation step (S2), and a multilayer extrusion molding step (S3). Each step will be described below.

[0092] <Biomass material drying process (S1)>

[0093] The biomass material used in this process is the same as that described in 1.(1) above, and therefore a detailed description of the biomass material will be omitted. In the biomass material drying step (S1), the biomass material is accommodated in a container. The container in which the biomass material is accommodated has a heat generating part for heating the inside of the container on the outside. An example of such a container is a heating mixer having a heating jacket around a cylindrical container made of stainless steel or steel. The heating mixer may have a housing part for housing the biomass material therein covered with a heating jacket on the outside. A stirring blade may be provided in the housing part. The heating jacket is filled with a heat medium such as oil, hot water or heated steam, and the heating jacket can function as a heat generating part. The heating jacket heats the housing part in the container by heating the inner surfaces such as the wall surface, the lid surface, and the bottom surface of the container. The heating jacket heats the inner surface of the container so that there are no insufficiently heated parts on the inner surface of the container. By preventing there from being any insufficiently heated parts on the inner surface of the container in this way, it is possible to suppress the moisture in the biomass material evaporated by heating from coming into contact with the insufficiently heated parts and condensing. By suppressing condensation on the inner surface of the heating mixer, it is possible to prevent the biomass material such as starch from gelatinizing and adhering to the inner surface of the heating mixer. The biomass material accommodated in the container is dried in the heated container. When drying the biomass material, the biomass material such as starch can be prevented from gelatinizing and drying efficiency can be improved by constantly moving the biomass material using an agitator blade. The shape of the agitator blade can be selected from any shape such as a propeller blade, a paddle blade, an inclined paddle blade, a turbine blade, a screw blade, an anchor blade, a ribbon blade, and a large lattice blade. Such a heating mixer is also called an external heating jacket type mixer.

[0094] In this step, from the viewpoint of efficiently drying the biomass material, the temperature inside the container is preferably 120° C. or higher, more preferably 135° C. or higher, and even more preferably 150° C. or higher. Furthermore, from the viewpoint of suppressing thermal deterioration of the biomass material, the temperature inside the container is preferably 200° C. or lower, more preferably 190° C. or lower, and even more preferably 180° C. or lower.

[0095] The stirring may be performed by setting the rotation speed of the stirring blade at preferably 500 to 2000 rpm, more preferably 750 to 1750 rpm, and further preferably 1000 to 1500 rpm.

[0096] In this step, the time for drying the biomass material is not limited, but can be appropriately set depending on the amount of the biomass material from the viewpoint of drying efficiency, for example, preferably 10 to 30 minutes, more preferably 15 to 30 minutes, and even more preferably 15 to 25 minutes.

[0097] In this process, the biomass material is prevented from adhering to the inner surface of the container in which the biomass material is contained. When the biomass material is heated in the container, the moisture contained in the biomass material evaporates. The evaporated moisture comes into contact with the parts of the inner surface of the container, such as the wall surface, the inner surface of the lid, and the bottom surface, in which the temperature rise due to heating is insufficient, and condensation occurs. In this process, the inside of the container is heated by a heating part provided on the outside, and there are no parts on the inner surface of the container where the temperature rise is insufficient, thereby suppressing the occurrence of condensation and preventing the biomass material in the container from adhering to the inner surface of the container. By preventing the biomass material from adhering to the inner surface of the container in this way, it is possible to efficiently produce a biomass material-containing layer with excellent quality. In addition, it is also preferable to prevent the biomass material from staying in one place by stirring the container in order to suppress the biomass material from adhering to the inner surface of the container.

[0098] The above uses an external heating jacket mixer, but a heating jacket vacuum dryer may be used in the biomass material drying step (S1) in this embodiment. This dryer is preferably equipped with an external heating jacket and has stirring blades in the container, and the biomass material can be dried by creating a vacuum in the container.

[0099] When a heating jacket type vacuum dryer is used, from the viewpoint of efficiently drying the biomass material, the temperature inside the container is preferably 100° C. or higher, more preferably 115° C. or higher, and even more preferably 130° C. or higher. Furthermore, from the viewpoint of suppressing thermal deterioration of the biomass material, the temperature inside the container is preferably 200° C. or lower, more preferably 185° C. or lower, and even more preferably 170° C. or lower.

[0100] The degree of vacuum inside the container is preferably set to 5 kPa to 30 kPa, more preferably 5 kPa to 25 kPa, and further preferably 5 kPa to 20 kPa.

[0101] In this step, the time for drying the biomass material is not limited, but can be appropriately set depending on the amount of the biomass material from the viewpoint of drying efficiency. For example, the time is preferably 30 to 90 minutes, more preferably 40 to 80 minutes, and even more preferably 50 to 70 minutes. In this step, the biomass material may be dried so that the moisture content is preferably 5% or less, more preferably 2% or less.

[0102] <Resin composition preparation process (S2)>

[0103] In the resin composition preparation step (S2), the biomass material dried in the drying step (S1) is mixed with a resin to prepare a biomass material-containing resin composition. In addition, an antistatic agent-containing resin composition is separately prepared. Note that the preparation of the antistatic agent-containing resin composition is the same as that described in 1.(3) above, and therefore the explanation of the preparation of the antistatic agent-containing resin composition is omitted.

[0104] In this process, when mixing the dried biomass material and the resin, for example, the dried biomass material and the resin may be simply mixed in a dry state to prepare a biomass material-containing resin composition which is a mixture of a powdered biomass material and a pellet-shaped resin. Alternatively, the dried biomass material and the resin may be simultaneously fed into an extruder via a feeder, and the biomass material and the resin may be uniformly kneaded and mixed by controlling the rotation speed, mixing time, temperature, etc., and heating and kneading, so that the mixture of the biomass material and the resin in a melt-kneaded state present in the extruder may be used as the biomass material-containing resin composition. Furthermore, the mixture of the biomass material and the resin in a melt-kneaded state may be extruded from the extruder, cooled, and pelletized to form the biomass material-containing resin composition. As such an extruder, a single-screw extruder or a twin-screw extruder may be used. In addition, when the biomass material and the resin are fed into the extruder, additives may be fed at the same time. Examples of such additives include low-melting point additives and high-melting point additives. Alternatively, the biomass material, resin, and additives may be added individually via feeders in predetermined blending amounts.

[0105] When the biomass material and the resin are mixed in the extruder, the heat processing temperature (cylinder temperature) may be set to a temperature lower than the temperature at which the resin melts or higher than the melting point of the high melting point additive, from the viewpoint of suppressing deterioration and discoloration of the materials. For example, the heat processing temperature (cylinder temperature) may be set to 100 to 190°C.

[0106] As the additive to be blended in this step, a low-melting additive that has a melting point lower than the melting temperature of the resin used in the biomass material drying step (S1) and melts at a relatively low temperature may be used.

[0107] The biomass material-containing resin composition may also contain a high-melting point additive having a melting point higher than that of the low-melting point additive. Note that the explanation of the low-melting point additive and the high-melting point additive in 1.(1) above applies to the low-melting point additive and the high-melting point additive, so the explanation of the low-melting point additive and the high-melting point additive is omitted.

[0108] As another additive, a compatibilizer can be used to improve the affinity between the biomass material and the resin. Note that the explanation of the compatibilizer in 1.(1) above applies to the compatibilizer, so the explanation of the compatibilizer is omitted here.

[0109] <Multi-layer extrusion molding process (S3)>

[0110] FIG. 2 is a schematic diagram showing an example of a multi-layer co-extrusion molding machine used in the method for producing an antistatic multi-layer sheet according to the second embodiment.

[0111] In the multilayer extrusion molding step (S3), an antistatic agent-containing resin composition different from the biomass material-containing resin composition is extruded, and the resin layer formed from the biomass material-containing resin composition and the resin layer formed from the antistatic agent-containing resin composition are laminated to obtain an antistatic multilayer sheet. The antistatic multilayer sheet can be obtained, for example, by using a multilayer co-extrusion molding machine 300 shown in FIG. 2. The multilayer co-extrusion molding machine 300 may have an extruder 301 for an A layer, an extruder 302 for a B layer, an extruder 303 for a C layer, a feed block 304, and a die 305. When producing an antistatic multilayer sheet having a two-layer structure, the multilayer co-extrusion molding machine 300 co-extrudes a two-layer structure sheet 306 in which the A layer and the B layer are laminated, with the B layer being a biomass material-containing layer and the A layer being an antistatic layer. The B layer extruder 302 extrudes the biomass material-containing resin composition prepared in the resin composition preparation step (S2), and the A layer extruder 301 extrudes the antistatic agent-containing resin composition extruded from the B layer extruder 302. In the multilayer sheet according to this embodiment, the average thickness of the biomass material-containing layer is preferably 300 μm or more, more preferably 350 μm or more, and even more preferably 400 μm or more, and preferably 1500 μm or less, more preferably 1400 μm or less, and even more preferably 1000 μm or less. The average thickness of the antistatic layer is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 50 μm or less.

[0112] The antistatic multilayer sheet according to the present embodiment can be produced by a lamination method (for example, a thermal lamination method and a dry lamination method) in addition to the multilayer coextrusion method described above. When using a lamination method, for example, the antistatic monolayer sheet or antistatic monolayer film according to the first embodiment is used as an antistatic layer, and the antistatic layer and a biomass material-containing layer are bonded together by heat or an adhesive to obtain an antistatic multilayer sheet. For example, the antistatic multilayer sheet 10 according to the present embodiment shown in FIG. 1 can be produced by bonding a biomass material-containing layer 11 and an antistatic layer 12 together by heat or an adhesive. The biomass material-containing layer may be produced by using the biomass material-containing resin composition used in the antistatic multilayer sheet according to the second embodiment instead of the antistatic agent-containing resin composition in the production method of the antistatic monolayer sheet or antistatic monolayer film according to the first embodiment.

[0113] 3. Third embodiment (another example of antistatic multilayer sheet)

[0114] (1) Composition of antistatic multi-layer sheet

[0115] The antistatic multilayer sheet according to the present embodiment has a biomass material-containing layer and antistatic layers formed on two main surfaces of the biomass material-containing layer. That is, the antistatic multilayer sheet according to the first embodiment is a multilayer sheet having a two-layer structure, whereas the antistatic multilayer sheet according to the present embodiment is a multilayer sheet having a three-layer structure. The antistatic multilayer sheet according to the present embodiment will be described below with reference to the drawings. FIG. 3 is a schematic cross-sectional view of the antistatic multilayer sheet according to the present embodiment. As shown in FIG. 3, the antistatic multilayer sheet 40 according to the present embodiment is an antistatic multilayer sheet having a three-layer structure including a biomass material-containing layer 42 and antistatic layers 41 and 43. The antistatic layers 41 and 43 are formed on two main surfaces of the biomass material-containing layer 42. Note that the description of the biomass material-containing layer and the antistatic layer in 2.(1) above applies to the biomass material-containing layer and the antistatic layer, so the description of the biomass material-containing layer and the antistatic layer will be omitted.

[0116] (2) Physical properties

[0117] As for the physical properties, the explanation of the physical properties in 2.(2) above applies, so the explanation of the physical properties will be omitted.

[0118] (3) Manufacturing method of antistatic multilayer sheet

[0119] The method for producing an antistatic multilayer sheet according to the third embodiment can include a biomass material drying step (S1), a resin composition preparation step (S2), and a multilayer extrusion molding step (S3).

[0120] The biomass material drying step (S1) and the resin composition preparation step (S2) are the same steps as those in the second embodiment, and therefore the explanations thereof will be omitted. The multi-layer extrusion molding step (S3) will be explained below.

[0121] <Multi-layer extrusion molding process (S3)>

[0122] In the multilayer extrusion molding step (S3), an antistatic agent-containing resin composition different from the biomass material-containing resin composition is extruded, and the resin layer formed from the biomass material-containing resin composition and the resin layer formed from the antistatic agent-containing resin composition are laminated to obtain an antistatic multilayer sheet. The antistatic multilayer sheet can be obtained, for example, by using a multilayer co-extrusion molding machine 300 shown in FIG. 2. The multilayer co-extrusion molding machine 300 may have an extruder 301 for an A layer, an extruder 302 for a B layer, an extruder 303 for a C layer, a feed block 304, and a die 305. The multilayer co-extrusion molding machine 300 co-extrudes an antistatic multilayer sheet 306 having a three-layer structure in which the A layer, the B layer, and the C layer are laminated, with the B layer containing a biomass material being the biomass material-containing layer, and the A layer and the C layer being the antistatic layers. The B layer extruder 302 extrudes the biomass material-containing resin composition prepared in the resin composition preparation step (S2), and the A layer extruder 301 and the C layer extruder 303 extrude antistatic agent-containing resin compositions prepared separately. In the antistatic multilayer sheet according to this embodiment, the average thickness of the biomass material-containing layer is preferably 300 μm or more, more preferably 350 μm or more, and even more preferably 400 μm or more, and preferably 1500 μm or less, more preferably 1400 μm or less, and even more preferably 1000 μm or less. The average thickness of the antistatic layer is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, and preferably 100 μm or less, more preferably 80 μm or less, and even more preferably 50 μm or less.

[0123] The antistatic multilayer sheet according to the present embodiment can be produced by a lamination method (for example, a thermal lamination method and a dry lamination method) in addition to the multilayer coextrusion method described above. When using the lamination method, for example, the antistatic monolayer sheet or antistatic monolayer film according to the first embodiment is used as an antistatic layer, and the antistatic layer and a biomass material-containing layer are bonded together by heat or an adhesive to obtain an antistatic multilayer sheet. For example, the antistatic multilayer sheet 40 according to the present embodiment shown in FIG. 3 can be produced by bonding a biomass material-containing layer 42, an antistatic layer 41, and an antistatic layer 43 together by heat or an adhesive. The biomass material-containing layer may be produced by using the biomass material-containing resin composition used in the antistatic multilayer sheet according to the second embodiment instead of the antistatic agent-containing resin composition in the production method of the antistatic monolayer sheet or antistatic monolayer film according to the first embodiment.

[0124] 4. Working Example

[0125] The present invention will be described in more detail below based on examples. Note that the examples described below are representative examples of the present invention, and the scope of the present invention is not limited to these examples. The evaluation methods and evaluation criteria used in the examples are as follows.

[0126] Example 1

[0127] 80 parts by mass of polyethylene (product name: EVOLUE SP0540, manufactured by Prime Polymer Co., Ltd.) and 20 parts by mass of a nonionic polymer-type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.) were compounded using a twin-screw extruder (Ikegai Corporation PCM30, screw diameter: 30φ) to obtain pellets. The obtained pellets were supplied to the B layer extruder 302 of the multilayer co-extrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in FIG. 2 through a hopper (not shown). The supplied antistatic agent-containing resin composition was co-extruded to obtain a single-layer sheet having a single-layer structure and an average thickness of 400 μm. The surface resistance value of the obtained single-layer sheet was 1010 After reheating at 200°C for 5 minutes, the surface resistance was 10 10 It was Omega.

[0128] Example 2

[0129] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that 20 parts by mass of an anionic polymer-type antistatic agent (product name: AS301E, manufactured by ADEKA Corporation) was blended instead of the nonionic polymer-type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The surface resistance value of the obtained single-layer sheet was 10 10 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0130] Comparative Example 1

[0131] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that 2 parts by mass of a nonionic surfactant A (trade name: LOXIOL (registered trademark) VPN176, manufactured by Emery Oleochemicals) was blended in place of a nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The surface resistance of the obtained single-layer sheet was 10 14 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0132] Comparative Example 2

[0133] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that 2 parts by mass of a nonionic surfactant B (trade name: LOXIOL (registered trademark) VPN180, manufactured by Emery Oleochemicals) was blended in place of a nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The surface resistance of the obtained single-layer sheet was 10 14 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0134] Comparative Example 3

[0135] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that 2 parts by mass of a nonionic surfactant C (trade name: LOXIOL (registered trademark) 8314, manufactured by Emery Oleochemicals) was blended in place of a nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The surface resistance of the obtained single-layer sheet was 10 14 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0136] Comparative Example 4

[0137] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that 2 parts by mass of a nonionic surfactant D (trade name: Rikemal (registered trademark) S-100, manufactured by Riken Vitamin Co., Ltd.) was blended instead of a nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The surface resistance value of the obtained single-layer sheet was 10 14 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0138] Comparative Example 5

[0139] A single-layer sheet having an average thickness of 400 μm was produced in the same manner as in Example 1, except that a nonionic polymer-type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.) was not blended. The surface resistance value of the obtained single-layer sheet was 10 14 After reheating at 200°C for 5 minutes, the surface resistance was 10 14 It was Omega.

[0140] Example 3

[0141] In a heating mixer (external heating jacket mixer, Kawata Co., Ltd.), 57 parts by mass of corn starch (manufactured by Showa Sangyo Co., Ltd.) with an initial moisture content of 14% and 0.6 parts by mass of glycerin fatty acid ester were mixed with a total of 100 parts by mass of each component (corn starch ratio before drying), and dried for 20 minutes at a heating jacket temperature of 150° C. The mixture of corn starch and low melting point additive obtained by the above mixing was transferred into a cooling mixer and cooled for 5 to 15 minutes until the material temperature of the mixture reached 20 to 40° C. Then, the mixture of the cooled corn starch and low melting additive, 19.2 parts by mass of polypropylene (trade name: CS356M, manufactured by Sunallomer Co., Ltd.), 10.1 parts by mass of polypropylene (trade name: FH1016, manufactured by Sumitomo Chemical Co., Ltd.), 1 part by mass of zinc stearate, 3 parts by mass of magnesium stearate, 3 parts by mass of styrene-based thermoplastic elastomer (trade name: Septon (registered trademark) 4033, manufactured by Kuraray Co., Ltd.), 3.1 parts by mass of maleic anhydride grafted polyolefin resin (trade name: Fusabond (registered trademark) N493, manufactured by DuPont Co., Ltd.), and 3 parts by mass of white pigment were compounded using a twin-screw extruder (Ikegai Co., Ltd. PCM30, screw diameter: 30φ) to obtain pellets. The obtained pellets were supplied to the B layer extruder 302 of the multilayer co-extrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) shown in FIG. 2 through a hopper.

[0142] In addition, 80 parts by mass of a polypropylene resin composition (product name: EG6D, manufactured by Japan Polypropylene Corporation) and 20 parts by mass of a nonionic polymer-type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.) were fed via a hopper to an extruder 301 for A layer of a multilayer coextrusion molding machine 300 (manufactured by LAB TECH Engineering Co., Ltd.) for the total mass of the polypropylene resin composition and the nonionic polymer-type antistatic agent, and 20 parts by mass of a polypropylene resin composition and a nonionic polymer-type antistatic agent were fed via a hopper to an extruder 303 for C layer. 80 parts by mass of a polypropylene resin composition (product name: EG6D, manufactured by Japan Polypropylene Corporation) and 20 parts by mass of a nonionic polymer type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.) were supplied relative to the total mass of the antistatic agent and the A layer extruder, the B layer extruder, and the C layer extruder were co-extruded to obtain a multilayer sheet with a three-layer structure in which the B layer, which is a biomass material-containing layer, is used as the middle layer and the A layer and the C layer, which are antistatic layers, are laminated on the two main surfaces of the B layer.

[0143] The cylinder temperature and adapter temperature of the A layer extruder 301 (model number: LE25-30 / C (LAB TECH Engineering), L / D: 30, φ: 250 mm), the B layer extruder 302 (model number: LE25-30 / C (LAB TECH Engineering), L / D: 30, φ: 250 mm), and the C layer extruder 303 (model number: LE25-30 / C (LAB TECH Engineering), L / D: 30, φ: 250 mm) were each set to 200 ° C. The screw speed of the B layer extruder 302 was 90 RPM, and the screw speed of the A layer extruder 301 and the C layer extruder 303 was 20 RPM.

[0144] By this multilayer extrusion molding, a sheet having an average thickness of 0.5 mm (hereinafter, also referred to as "multilayer sheet of Example 3") was obtained. The average thickness of the A layer was 35 μm, the average thickness of the B layer was 430 μm, and the average thickness of the C layer was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of the A layer and the C layer were both 10 10 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14It was Omega.

[0145] Example 4

[0146] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Example 4") was obtained in the same manner as in Example 3, except that 20 parts by mass of an anionic polymer-type antistatic agent (product name: AS301E, manufactured by ADEKA Corporation) was blended instead of the nonionic polymer-type antistatic agent (product name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The average thickness of layer A was 35 μm, the average thickness of layer B was 430 μm, and the average thickness of layer C was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of layers A and C were both 10 10 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0147] Comparative Example 6

[0148] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Comparative Example 6") was obtained in the same manner as in Example 3, except that only the polypropylene resin composition was supplied to each of the extruder 301 for A layer and the extruder 303 for C layer via a hopper. The average thickness of the A layer was 35 μm, the average thickness of the B layer was 430 μm, and the average thickness of the C layer was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of the A layer and the C layer were both 10 14 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0149] Comparative Example 7

[0150] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Comparative Example 7") was obtained in the same manner as in Example 3, except that 2 parts by mass of nonionic surfactant A (trade name: LOXIOL (registered trademark) VPN176, manufactured by Emery Oleochemicals) was blended instead of the nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The average thickness of layer A was 35 μm, the average thickness of layer B was 430 μm, and the average thickness of layer C was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of layers A and C were both 10 14 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0151] Comparative Example 8

[0152] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Comparative Example 8") was obtained in the same manner as in Example 3, except that 2 parts by mass of nonionic surfactant B (trade name: LOXIOL (registered trademark) VPN180, manufactured by Emery Oleochemicals) was blended in place of the nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The average thickness of layer A was 35 μm, the average thickness of layer B was 430 μm, and the average thickness of layer C was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of layers A and C were both 10 14 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0153] Comparative Example 9

[0154] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Comparative Example 9") was obtained in the same manner as in Example 3, except that 2 parts by mass of nonionic surfactant C (trade name: LOXIOL (registered trademark) 8314, manufactured by Emery Oleochemicals) was blended instead of the nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The average thickness of layer A was 35 μm, the average thickness of layer B was 430 μm, and the average thickness of layer C was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of layers A and C were both 10 14 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0155] Comparative Example 10

[0156] A sheet having an average thickness of 0.5 mm (hereinafter also referred to as "multilayer sheet of Comparative Example 10") was obtained in the same manner as in Example 3, except that 2 parts by mass of nonionic surfactant D (trade name: Rikemal, S-100, manufactured by Riken Vitamin Co., Ltd.) was blended instead of the nonionic polymer-type antistatic agent (trade name: Pelestat (registered trademark) 230, manufactured by Sanyo Chemical Industries, Ltd.). The average thickness of layer A was 35 μm, the average thickness of layer B was 430 μm, and the average thickness of layer C was 35 μm. In the obtained multilayer sheet, the surface resistance values ​​of layers A and C were both 10 14 After reheating at 200°C for 5 minutes, the surface resistance of both layers A and C was 10 14 It was Omega.

[0157] The configurations, methods, steps, shapes, materials, and values ​​described in the above-described embodiments and examples are merely examples, and different configurations, methods, steps, shapes, materials, and values ​​may be used as necessary.

[0158] Furthermore, the configurations, methods, processes, shapes, materials, numerical values, and the like of the above-described embodiments and examples can be combined with each other without departing from the spirit and scope of the present technology.

[0159] In addition, in this specification, a numerical range indicated using "~" indicates a range including the numerical values ​​described before and after "~" as the minimum and maximum values, respectively. In a numerical range described in stages in this specification, the upper limit or lower limit of a numerical range in a certain stage may be replaced with the upper limit or lower limit of a numerical range in another stage. Unless otherwise specified, the materials exemplified in this specification may be used alone or in combination of two or more types. [Explanation of symbols]

[0160] 300 Multi-layer Co-extrusion Machine 301 A layer extruder 302 B layer extruder 303 C layer extruder 304 Feedblock 305 Dice

Claims

1. An antistatic single-layer sheet or film formed from an antistatic agent-containing resin composition that contains a polymer-type antistatic agent.

2. 2. The antistatic single-layer sheet or film according to claim 1, wherein the polymer-type antistatic agent is a nonionic polymer-type antistatic agent.

3. 3. The antistatic monolayer sheet or film according to claim 2, wherein the nonionic polymeric antistatic agent has a polyethylene oxide chain incorporated therein.

4. At least one of the main surfaces has a surface resistance of 10 12.5 2. The antistatic monolayer sheet or film according to claim 1, having a resistance of Ω or less.

5. 2. The antistatic monolayer sheet or film according to claim 1, having an average thickness of 1500 μm or less.

6. After heating for 5 minutes in a 200° C. environment, the surface resistance of at least one of the main surfaces is 10 12.5 2. The antistatic monolayer sheet or film according to claim 1, having a resistance of Ω or less.

7. a biomass material containing layer; an antistatic layer formed on at least one major surface of the biomass material-containing layer; A multilayer sheet having The biomass material-containing layer is formed from a biomass material-containing resin composition containing a biomass material, The antistatic multilayer sheet, wherein the antistatic layer is formed from an antistatic agent-containing resin composition that contains a polymer-type antistatic agent.

8. 8. The antistatic multilayer sheet according to claim 7, wherein the polymeric antistatic agent is a nonionic polymeric antistatic agent.

9. 9. The antistatic multilayer sheet according to claim 8, wherein the nonionic polymeric antistatic agent has polyethylene oxide chains incorporated therein.

10. At least one of the main surfaces has a surface resistance of 10 12.5 8. The antistatic multilayer sheet according to claim 7, wherein:

11. 8. The antistatic multilayer sheet according to claim 7, wherein the average thickness of the antistatic layer is 100 [mu]m or less.

12. After heating for 5 minutes in a 200° C. environment, the surface resistance of at least one of the main surfaces is 10 12.5 8. The antistatic multilayer sheet according to claim 7, having a resistance of Ω or less.

13. 8. The antistatic multilayer sheet of claim 7, wherein the biomass material is starch.

14. The antistatic multilayer sheet according to claim 7 , wherein the antistatic layers are formed on both major surfaces of the biomass material-containing layer.

Citation Information

Patent Citations

  • Polypropylene composition having biochemical degradability and its production

    JP2001064458A

  • Biodisintegradable sheet and its manufacturing method

    JP2004155842A